U.S. Federal Budget Deficits and Gramm-Rudman-Hollings - Grämlich, Edward M. (American Economic Review, 1990)
The U.S. federal budget deficits averaged about 1 percent of GNP in the 1960s, about 2 percent of GNP in the 1970s, and then rose to a peak of 5.5 percent of GNP in the four bad years of fiscal 1983 to fiscal 1986. By fiscal 1989, they had fallen back to 2.9 percent of GNP, and under present legislation they are now projected to drop to about 1.5 percent of GNP by 1994. When deficits were at their peak, before the start of the budget bargain for fiscal 1987 (the first budget to show any sizeable deficit reduction), the country passed the GrammRudman-Hollings (GRH) deficit control law. This law has been revised and amended over time, but it is still operating in roughly its initial form. Superficially, the numbers given above suggest that it must be working pretty well. Moreover, in many ways GRH was written to respond to the standard criticisms of deficit constraint legislation: it did not call for abrupt cuts in deficits but rather gradual declines, it was legislative and flexible rather than constitutional and rigid. Yet just as the country is on the verge of finally getting its deficits under control, the legislation is coming under vicious attack, including even that of one of its sponsors, Senator Hollings. Why should such an apparently successful piece of legislation be so widely scorned? In this paper I take on this question. I first illustrate how GRH was intended to operate with a simple indifference curve model, and use this model to see what kinds of changes should have occurred in budget bargains and spending patterns. Then I look for these changes by comparing numbers from the pre-GRH era (1983-86) with those from the post-GRH era (1987-89). I also identify other sources of improvement in budgetary position from the earlier to the later period. This numerical comparison suggests that the direct effects of GRH played a very minor role in the improvement in the U.S. budgetary position, though it seems likely that difficult to evaluate indirect effects were much more significant.